Palatal rhinosporidiosis: an unusual case report and review of the literature - Putthia, Harshita (J Korean Assoc Oral Maxillofac Surg, 2018)
Rhinosporidiosis is a chronic, granulomatous, mucocutaneous infection caused by Rhinosporidium seeberi . The infection is non-contagious and sporadic in humans. The site most commonly affected is the mucous membrane of the nose and nasopharynx, followed by the oropharynx, trachea, bronchi, ear, eye, and genitourinary tract. It can also spread to other areas through blood and lymph. Here, we report a case of rhinosporidiosis affecting the palate in a 60-year-old female patient.